Slovenska tranzicija v kontekstu krize svetovno-sistemskega akumulacijskega cikla - Klarič, Matej (visokošolska dela, 2021)
In 2008, the world was shaken by the biggest crisis of capitalism since the Great Depression of the late 1920s and 1930s. For most of the expert community, it was a massively unexpected event, as the leading economic models had assumed no crisis of such magnitude could ever again be possible; indeed, the market was expected to automatically prevent any excessive fluctuations that could lead to it. Thus, due to the unwavering belief in the power of the free market, the sheer scope, depth, and duration of the crisis were completely unforeseen. Moreover, the 2008 crisis turned upside down the very theory on which politicians had shaped their political-economic orientations, i.e., the neoliberal ideology that promoted the policies of deregulation, privatization, tax cuts, etc. Similarly, in line with the theory of the end of history and of only one possible path, the transition of the formerly socialist countries into capitalist economies was understood mostly as a transition from the failed socialist systems to the timeless system ruled by the free market. The latter was believed to be the best possible regulator of socio-economic fluctuations. In this sense, the dominant (economic) ideas associated transition with a process of a one-way transition from inefficient historical socialisms to the capitalist system of a market economy as the final stage of all societies developed to their highest stage. Unlike in the case of the dominant neoclassical economic theories outlined above, the crisis did not come as a shock to the World-Systems Theory. Rather, the latter see crises as an inevitable phenomenon, resulting from capitalist contradictions within individual cycles of accumulation. As historical analysis demonstrates, each of the cycles so far has been characterized in its first phase by material expansion, and in its second phase, by a shift to financial capital. In the past, the second phase also always simultaneously meant a decline of the hegemonic state within an individual cycle. Contrary to the dominant ideas of today, the World-System Theory offers evidence not only of the inevitable nature of crises in capitalism, but also of the fact that the period of financialization that has characterized the second phase of the American accumulation cycle is nothing new when seen from the historical perspective. On the contrary, it is just another cyclical repetition of the two phases in a single cycle that has thus far, every time progressed to encompassing an ever-greater part of the world and more actors than before. In relation to the Slovene transition, this leads to an important finding. Since every period of financial expansion, which always started with a signal crisis and announced its ending with a terminal crisis, also meant a transition or in other words, a transformation of the whole system into something new, it can be argued that the period since the most recent terminal crisis of 2008 can likewise be considered an indicator of major global changes underway. This means that not only former socialist countries, but the whole system is in a transition – turning upside down the leading theories of transition that measure countries’ success mostly by their adaptation to neoliberal political solutions, regardless of the negative effects those policies bring along. In this context, a different understanding of transition opens a new perspective of the past and current processes in Slovenia, in other post-socialist countries, as well as elsewhere in Europe, and the world. Seen in this way, the occurring changes are no longer part of an inevitable path in the direction of neoliberal reforms, but are themselves part of a problem, reflected in different parts of the world in ever-increasing social tensions, unrest and new (especially far-right) political groupings; a direct response to the dissatisfaction of the masses, their unfulfilled expectations and promises broken by the neoliberal model of capitalism. Thus, through interdisciplinary and historical analysis based on the above-described theoretical apparatus, this doctoral dissertation defines the Slovene transition differently, placing it in a larger timeframe, to obtain a more holistic understanding of the processes taking place not only in Slovenia but also more broadly. The processes in a system as interconnected as the global capitalism of the American accumulation cycle namely cannot be treated separately, limited to a single country, and within a strictly confined timeframe that leaves out more long-term processes, understanding history only as a series of related events. Therefore, apart from taking into consideration a longer period leading to Slovenia’s independence, systemic factors related to capitalist systemic cycles of accumulation have also been added to the existing analyses of the country’s transition (that mostly deal with internal factors in the post-independence period), while simultaneously emphasizing the importance of external factors on internal political-economic developments, based on a broader perspective. Notably, external factors and major structural geopolitical changes tend to be pushed to the side or completely neglected when it comes to analyses of Yugoslavia’s disintegration. In this aspect, this doctoral dissertation offers a different, more comprehensive perspective that considers and relates the external factors to the systemic cycles of accumulation, while simultaneously taking note of the particularities of the Slovene situation. Considering these points, the transition of the system had not only begun with independence but already in socialist Yugoslavia, when the latter was in the 1980s reached with a delay, by the global processes of the 1970s signal crisis. Typically, the reasons for the breakup of Yugoslavia tend to be discussed mostly in relation to its over-indebtedness and the nationalist aspirations of its individual states, which through the gaining of independence essentially fulfilled their 'thousand-year dream.' Notwithstanding, seen in relation to the developments in the international environment, the story of Yugoslavia indicates that international institutions and the changes in the international environment directly resulting from the signalling crisis, and followed by the shift to financialization, played an important role in Yugoslavia’s breakdown. Political decisions taken in the centers of global power led to measures that caused a deterioration in the situation for people in various parts of the world. Often these changes that followed the collapse of the Bretton Woods Agreement (from an increase in the cost of borrowing, to conditions attached to loan approval, and the imposition of austerity measures which, with the deterioration of the situation in Yugoslavia, provided fertile ground for the expansion of nationalisms in the country) are completely overlooked. The bloody Balkan wars ensued, which unlike some other states of the former Yugoslavia, Slovenia managed to avoid with only a brief war. The Slovene post-independence story was unique and deviated from the transition processes in the rest of the post-socialist states, which fervently followed the radical neoliberal shock doctrine. In a concentrated period after 1991, Slovenia was developing in line with the paradigm typical of the US systemic cycle of accumulation that prevailed after WW2. From 1991 to 2004, akin to Europe in WW2’s aftermath and up until the 1970s, Slovenia was developing in line with the neo-corporate model. Unlike other post-socialist states, it was pushed into this direction especially by strong trade unions, by the legacy of socialism, and the electoral system based on proportional representation, which forced political parties into considering wider social interests, and directed them to cooperate to form government coalitions. The power of the trade unions thus made it easier for them to compel the government to take their interests into consideration. Just like in Europe in the times of post-war Keynesianism, policy formation would take place based on tripartite negotiations between trade unions, the government, and employers. Moreover, the policies were based on promoting full employment, wage growth, and similar. Notably, this was the time when Slovenia was achieving enviable results that were sometimes described as a success story, mainly due to positive economic indicators. Nonetheless, this changed with Slovenia’s accession to the EU in 2004, when the above-described development model came to an end. That year’s elections were marked by a victory of a center-right coalition and a turn to the neoliberal doctrine in the government policy. The shift resembled the one occurring in the 1970s in the West, after the signaling crisis, albeit for slightly different reasons. While at the global level, the cause of the changes taking place was the crisis of the US systemic cycle of accumulation that pushed the system into the phase of financialization, in Slovenia that change was caused primarily by the external factors pressing the country to pass the measures required for the accession to the EU and the eurozone. Slovenia lost some of its macroeconomic mechanisms in the fiscal and monetary areas (customs tariffs, the tools to drive inflation, and especially the mechanism for currency devaluation). Before, these tools made it possible for it to pursue autonomous Keynesian policies. Nevertheless, in large part due to these structural changes resulting from the country becoming part of the EU, and thus complying with the neoliberal rules enshrined in its documents, these mechanisms had to be abandoned. Thus, Slovenia lost a part of its sovereignty – even though the latter was one of the main motivations for its move to independence. At the height of the crisis, there was a string of short-lived governments; each early election brought with it fresh faces with new (unfulfilled) promises of different policies. The general state of frustration with politics was strong, due to rising unemployment and poverty, and shrinking pensions, wages, and other benefits. Nevertheless, different governments were still pursuing the path of radical neoliberal policies that were, along with increasingly more expensive borrowing, imposed by international (particularly European) institutions. In such circumstances, the space for different policies was even more limited than after Slovenia joined the eurozone. The crisis only began to subside by the end of 2014. Since then, Slovenia has recorded one of the highest growth rates in the EU, however, this has only benefited a well-off minority of the population. Despite the encouraging economic trends and the normalization of the situation in Slovenia, global and regional tensions arising from the crisis of the US systemic cycle of accumulation have not subsided. Far-right policies that point to migrations as the main culprit for the systemic problems are again experiencing an ever-increasing rise in popularity, like the crisis times of the British systemic cycle of accumulation, albeit in slightly changed circumstances. As has been noted, the systemic crisis heralds major changes in the second phase of the US systemic cycle of accumulation that will sooner or later bring an end to the hegemony of neoliberalism. Indeed, at the global level, the crumbling of the neoliberal consensus and the decline of American power can be seen as a prediction of a more radical turn. In this context, the transition can be understood from a much broader perspective. It involves not only Slovenia but the entire world-system. This further raises a key question about the future development of not only Slovenia but of the whole world. Due to numerous factors, it is impossible to predict what direction these processes will lead in the future. In these developments, Slovenia is only a small actor that should be aware of the changes and respond to them prudently. The way in which the transition will affect it will depend on the characteristics of the Slovene systemic cycle of accumulation and its structural weaknesses. Given the historical experience, it is very likely that we are witnessing the end of US hegemony within capitalism. While the capitalist system could persist, if a new systemic cycle of accumulation takes place, with a new hegemon replacing the USA, there is another perfectly possible outcome: the end of capitalism, and the rise of a different system, not necessarily more egalitarian.
Keywords: ameriški akumulacijski cikel; Disertacije; Ekonomija; ekonomski sistemi; Kapitalizem; keynesianizem; neoklasična ekonomija; Neoliberalizem; politična ekonomija; tranzicija